KEADAAN KELOMPOK TANI HUTAN RIN PAMU PENYADAP GETAH PINUS DI DESA TOMBASIAN ATAS SATU KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - Alicia Magdalena Kwiryn Koloy; Jane Sulinda Tambas; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2021)
This study aims to identify and describe the condition of the Rin Pamu forest farmer group tapping pine resin in Tombasian Atas Satu Village, Kawangkoan Barat District, Minahasa Regency. Condition are the situation in pine resin tapping related to labor, transportation, road access, income, companiy, government and environmental conditions. The research was conducted from March to May 2021. The data used in this study were primary and secondary data. Sampling used purposive sampling method. Interview conducted to 7 forest farmers as informants. The method used in this study is a descriptive method through a qualitative approach. The research results showed that workers from forest farmer groups still need to be assisted by expert workers, from company, to improve the quality of the tapped pine resin, the transportation used by members of the tapping farmer groups is a trail bike that has been modified to suit the conditions of steep unpaved road access, the income earned by the tappers is in accordance with the number of days they go to tap so that they tend to be unstable, the company is a partner of forest farmers who provide assistance and equipments, the government provides permits and equipments and environmental conditions, especially in hot weather, the amount of pine resin that is tapped. more than rainy and windy weather.*eprm*